Purification of benzene fractions and benzene from unsaturated and sulfur compounds using a novel modified natural clay-based adsorbent - B. Yu. Malyshkin; I. P. Semenov; D. S. Sazonov; I. O. Putenikhin; E. Yu. Semenikhina (Тонкие химические технологии)
Objectives. This study aimed to create a method for purifying benzene fractions using a modified natural clay-based adsorbent, which removes both unsaturated and sulfur compounds from benzene or benzene fractions obtained by pyrolysis of petrochemical raw materials.Methods. Chemical and chromatographic methods were used to conduct flow analyses before and after purification. Testing was conducted under conditions that were similar to industrial conditions. The functional characteristics of the adsorbents (moisture resistance and bulk density) were evaluated by strength tests after wetting with water and by weighing batches of the adsorbents fixed in volume.Results. Three clay-based adsorbent samples were developed, and tested under laboratory conditions. Thereafter, the CS-Sorb-6890 (M) sample—an Ni-modified adsorbent—was tested under experimental industrial conditions. A positive effect was obtained, and a method for purifying benzene fractions (benzene) from sulfur compounds and olefins is proposed.Conclusions. The obtained results revealed that the modified active clay-based adsorbent successfully removed sulfur and unsaturated compounds from the benzene fraction simultaneously. The total sulfur concentration was reduced to 0.00004 wt % after 90% of it was removed. The conversion of the unsaturated compounds reached 100%.